2019
DOI: 10.1021/acsnano.9b03900
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Confined Polyelectrolyte Conformations through Dielectric Mismatch

Abstract: We demonstrate that a highly charged polyelectrolyte confined in a spherical cavity undergoes reversible transformations between amorphous conformations to a four-fold symmetry morphology as a function of dielectric mismatch between the media inside and outside the cavity. Surface polarization due to dielectric mismatch exhibits an extra "confinement" effect, which are most pronounced within a certain range of the cavity radius and the electrostatic strength between the monomers and counterions and multivalent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…In contrast to bulk solutions, polyelectrolytes in confinement and in presence of dielectric mismatch conditions show a transitional behavior into various conformations. Here, surface polarization mechanisms as induced by a dielectric mismatch in combination with the electrostatic interactions between the monomers and multivalent counterions favor changes in the conformational behavior when compared to bulk conditions [102]. The corresponding findings reveal that specifically also the conformational properties of the polyelectrolyte are modified by distinct charge states, multivalent ions, dielectric mismatch conditions as well as the presence of confinement effects and high salt and polyelectrolyte concentrations.…”
Section: Specific Ion Effectsmentioning
confidence: 80%
“…In contrast to bulk solutions, polyelectrolytes in confinement and in presence of dielectric mismatch conditions show a transitional behavior into various conformations. Here, surface polarization mechanisms as induced by a dielectric mismatch in combination with the electrostatic interactions between the monomers and multivalent counterions favor changes in the conformational behavior when compared to bulk conditions [102]. The corresponding findings reveal that specifically also the conformational properties of the polyelectrolyte are modified by distinct charge states, multivalent ions, dielectric mismatch conditions as well as the presence of confinement effects and high salt and polyelectrolyte concentrations.…”
Section: Specific Ion Effectsmentioning
confidence: 80%
“…Polymers 2020, 12, x FOR PEER REVIEW 5 of 22 We have reported results regarding simulations of PGA and PASA in water already earlier [57]. The addition of divalent CaCl2 salt in solution causes changes in chain conformations due to ion adsorption (Figure 2).…”
Section: Results From Classical Unbiased MD Simulationsmentioning
confidence: 99%
“…Conformations of polyelectrolyte chains play an important functional role [ 20 , 21 , 22 ]. Adsorption of multivalent cations on a polyelectrolyte chain may lead to significant changes in their sizes and conformations [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, for many biological settings as well as in supercapacitor applications, molecular electrolytes confined by dielectric materials, such as graphene, are of interest. Recent studies on dielectric confinement of polyelectrolyte by a spherical cavity showed that dielectric mismatch leads to unexpected symmetry-breaking conformations, as the surface charge density increases (20). The focus of the present study is the collective effects of spatial confinement by two parallel surfaces and dielectric mismatch on the structural features of a polyelectrolyte solution.…”
mentioning
confidence: 93%